Analysis Of Korteweg-Type Compressible Fluid Model With Slip Boundary Conditions In 3-Dimensional Half-Space - Inna, Suma; Manaqib, Muhammad; Gifari, Ilman (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
AbstractThe Korteweg fluid model is typically used to describe the flow of two-phase fluids, where phase transitions occur at the interface, recognized by capillary effects. Korteweg extended the Navier-Stokes equations by incorporating capillarity into the equations. This article will demonstrate the solution operator for the resolvent system of the Navier-Stokes-Korteweg model with slip boundary conditions in a 3-dimensional half-space, given the coefficient condition  dengan . The steps to find the solution operator for the resolvent system include reducing the inhomogeneous resolvent system, followed by performing a partial Fourier transform on the homogeneous resolvent system to yield a simple ordinary differential equation solution.